The Nonmetabolized β-Blocker Nadolol Is a Substrate of OCT1, OCT2, MATE1, MATE2-K, and P-Glycoprotein, but Not of OATP1B1 and OATP1B3 - Misaka, Shingen; Knop, Jana; Singer, Katrin; Hoier, Eva; Keiser, Markus; Müller, Fabian; Gläser, Hartmut; König, Jörg; Fromm, Martin (Molecular Pharmaceutics, 2016)
Nadolol is a nonmetabolized ?-adrenoceptor antagonist and is a substrate of OATP1A2, but not of OATP2B1. However, other drug transporters involved in translocation of nadolol have not been characterized in detail. We therefore investigated nadolol as a potential substrate of the hepatic uptake transporters OATP1B1, OATP1B3, and OCT1 and of the renal transporters OCT2, MATE1, and MATE2-K expressed in HEK cells. Moreover, the importance of P-glycoprotein (P-gp) for nadolol transport was studied using double transfected MDCK-OCT1-P-gp cells. Nadolol was not transported by OATP1B1 and OATP1B3. In contrast, a significantly higher nadolol accumulation (at 1 and 10 ?M) was found in OCT1, OCT2, MATE1, and MATE2-K cells compared to control cells (P < 0.01). Km values for OCT2-, MATE1-, and MATE2-K-mediated nadolol uptake were 122, 531, and 372 ?M, respectively. Cimetidine (100 ?M, P < 0.01) and trimethoprim (100 ?M, P < 0.001) significantly inhibited OCT1-, OCT2-, MATE1-, and MATE2-K-mediated nadolol transport. The P-gp inhibitor zosuquidar significantly reduced basal to apical nadolol transport in monolayers of MDCK-OCT1-P-gp cells. In summary, nadolol is a substrate of the cation transporters OCT1, OCT2, MATE1, MATE2-K, and of P-gp. These data will aid future in vivo studies on potential transporter-mediated drug-drug or drug-food interactions with involvement of nadolol.
EVALuna2:8690